Women, gender and drugs: between research and action - Anne Coppel; Sarah Perrin (Harm Reduction Journal)
Abstract This article is part of Harm Reduction Journal’s special issue on harm reduction research in the francophone context and specifically the Harm Reduction Network (HARENE). After highlighting the history and current context of harm reduction for women in France, we present the results of four research studies addressing the links between gender and drugs which were presented in the book Espaces genrés des drogues. Parcours dans la fête, l’intimité et la réduction des risques (‘Gendered Spaces of Drugs. A journey of intimacy, party and harm reduction’). This article is divided into three parts, each addressing a specific space: the space of institutional care, the intimate marital space, and the urban festive space. We begin by describing gender inequalities within harm reduction and care structures, by demonstrating how single-sex spaces facilitate the care of women, and how care professionals can perpetuate unequal gender norms in their relationship with a woman in a situation of addiction expressing a desire for pregnancy. Concerning the marital space, we highlight the reproduction of gender norms within socially included heterosexual couples who use drugs and are socially included, particularly concerning the choice of the intimate partner, the distribution of tasks linked to the purchase and sale of drugs, and parenthood. Finally, concerning the festive space, the article highlights the differentiated strategies of men and women in urban festive places, and the maintenance of a gendered order of festive places and drug consumption. This leads us to discuss the current issues of stigmatization of women drug users, and the initiatives put in place in the French context to promote harm reduction for women who use drugs.